Fekete–Szegö Inequality for Bi-Univalent Functions Subordinate to Horadam Polynomials. (27th January 2022) - Shammaky, Amnah E.; Frasin, Basem Aref; Swamy, Sondekola Rudra
Abstract : Making use of Horadam polynomials, we propose a special family of regular functions of the type g z = z + ∑ j = 2 ∞ d j z j which are bi-univalent (or bi-schlicht) in the disc z ∈ ℂ : z < 1 . We find estimates on the coefficients d 2 and d 3 and the functional of Fekete–Szegö for functions in this subfamily. Relevant connections to existing results and new observations of the main result are also presented.